The national parks. Episode two, The last refuge (1890-1915) [videorecording (DVD)] : America's best idea - Burns, Ken, 1953-; Coyote, Peter; Muir, John, 1838-1914; Grinnell, George Bird, 1849-1938; Roosevelt, Theodore, 1858-1919 (PBS Home Video ; Distributed by Paramount Home Entertainment, 2009)
By the end of the 19th century, widespread industrialization has left many Americans worried about whether the country will have any pristine land left. At the same time, poachers in the parks are rampant, and visitors think nothing of littering or carving their names near iconic sites like Old Faithful. Congress has yet to establish clear judicial authority or appropriations for the protection of the parks. This sparks a conservation movement by organizations such as the Sierra Club, led by John Muir; the Audubon Society, led by George Bird Grinnell; and the Boone and Crockett Club, led by Theodore Roosevelt. The movement fails, however, to stop San Francisco from building the Hetch Hetchy Dam at Yosemite, flooding Muir's "mountain temple" and leaving him broken-hearted before he dies.